Mengkomunikasikan Penjualan Emas PT. Pegadaian Syariah di Jakarta Barat - NW Dewi Susanti (Jurnal Visi Komunikasi, 2020)
PT. Pegadaian Syariah in increasing gold sales by communicating gold products to consumers, so that consumers after knowing the advantages of buying gold become a profitable purchase option. The problems in this research; how PT. Pegadaian Syariah communicates products, advantages and services in selling gold to consumers and potential consumers. The company's marketing communication process to consumers with the aim of increasing understanding, attracting buying interest and increasing sales of gold products can be achieved. Qualitative research methods - a case study used to research with descriptive design and data collection techniques with participatory observation, in-depth interviews, and documentation study. Companies in increasing sales to consumers by communicating variations of precious metal gold products, prices, procedures for calculating precious metal gold investment through brochures, price tables, promotions through advertising, personal selling, face-to-face communication / direct selling, to consumers who make purchases, seminars and Pegadaian Digital Service (PDS) in the form of web and mobile-based applications. Consumer backgrounds determine how to make purchases and the reasons for consumer purchases vary, so that marketing communication methods are always adapted to the unique needs of consumers.